PENGARUH KOMPENSASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT. Y DI DAERAH CIPUTAT TANGERANG SELATAN - Afifah Agustina; Fetty Fauziah; Maeta Rahma Sari; Rezi Hernandi; Rizky Zaenal Mustofa (Journal of Research and Publication Innovation, 2025)
This Research aims to determine the effect of compensation and discipline on employee performance at PT Y in the Ciputat area of South Tangerang. This study uses a descriptive analysis research design with the use of quantitative/statistical data collection. The sample in this study was taken using a saturated sample, namely the number is the same as the population of 60 people. The results of this study are t-count 1.707> 1.992. Then it can be seen that the significant value of work discipline with employee performance is 0.132> 0.05, therefore Ho is rejected and Ha is accepted, meaning there is no influence between Compensation and employee performance.